Повышение эффективности работы тепловых сетей при регулировании тепловой нагрузки на вводах потребителей - Бердышев, Николай Юрьевич; Жадик, Артем Юрьевич (Национальный технический университет "Харьковский политехнический институт", 2019)
Приведен регрессионный анализ работы трех крупных котельных г. Мариуполь в отопительном сезоне 2016–2017 года. Показано, что имеет место достаточная взаимосвязь между расходом воды и градусо-сутками, то есть регулирование на этих котельных осу-ществляется не только качественном способом, но и частично количественным. Предложена автоматизированная малая котельная, в которой за счет частотного регулирования параметров сетевого и подпиточного насосов поддерживается постоянное давление в сети, так что при изменении расхода теплоносителя у определенного потребителя уменьшается расход в сети почти без повышения расхода у остальных потребителей. При этом экономия отпущенной теплоты на котельной практически равна экономии теплоты у потребителя, который уменьшил расход теплоносителя. Работоспособность предложенной схемы доказана на примере работы экспериментальной установки.

The regression analysis of the work of three large boiler houses in the city of Mariupol in the heating season 2016–2017 is given. It is shown that there is a sufficient relationship between water consumption and degree-times, that is, regulation at these boiler houses is carried out not only qualitatively but also partially quantitative. At all these boiler-houses in the transition period (March), the consumption of network water is approximately 15 % less than in winter. An automated small boiler house is proposed in which the constant network pressure is maintained at the expense of frequency regulation of the network and feeder pumps, so that when the heat carrier's consumption changes with a particular customer, the consumption of the network decreases almost without increasing the cost to the rest of the consumers. At the same time, the savings of the released heat at the boiler house is practically equal to the user's saving of heat, which reduced the consumption of coolant. The efficiency of the proposed scheme is proved by the example of the experimental setup. Conclusion: equipping a network pump on small boilers with frequency regulation of the speed of rotation makes it possible to virtually eliminate redistribution of the coolant between neighboring consumers with a reduction in the consumption of an individual consumer and to save not only electric energy but also fuel.
Improvement of efficiency of thermal network operation under thermal load regulation on the thermal inputs of consumers
Keywords: централизованное теплоснабжение; количественное регулирование; регрессионная линия; частотный регулятор; обратный клапан; циркуляционный насос; гидравлический режим; centralized heat supply; quantitative regulation; regression line; frequency controller; check valve; circulation pump; hydraulic mode